Los medios y los modos : participación política y acción colectiva de las mujeres - Massolo, Alejandra (Book collections on Project MUSE., 1994)
"Collection of five articles aims to debunk myth that political issues are not relevant to women by demonstrating women's leading roles in various social and political efforts. Two papers focus on women in the Partido Acción Nacional who are organizing against election fraud in Ciudad Juárez. Other articles examine Movimiento Urbano Popular in Veracruz, action networks in Mexico City, and a women's resistance organization in the mining community of Cananea, Sonora"--Handbook of Latin American Studies, v. 57.